Study and comparison results of the field oriented control for photovoltaic water pumping system applied on two cities in Morocco - Mustapha Errouha; Aziz Derouich (Bulletin of Electrical Engineering and Informatics, 2019)
In this papier, a low-cost solar photovoltaic water pumping system based on an induction motor without the use of chemical energy storage is presented. In literature, we can find several Maximum Power Point Tracking Algorithms, the choice of the algorithm is according to the nature of application. In this article, Variable Step Size Incremental Conductance MPPT method has been developed since it is fast and has less oscillations. The studied photovoltaic pumping system contains a centrifugal pump which is driven by a three-phase asynchronous motor. To control the water flow, the field-oriented control has been implemented. The control system is applied on two cities with different climatic conditions to evaluate their performance. The photovoltaic pumping system is developed using the MATLAB/Simulink software to discuss the results obtained. Consequently, the proposed MPPT based on the incremental conductance variable step shows good performances in terms of efficiency and tracking speed.